Una mirada al mercado de productos financieros “Caso del Pequeño Inversionista en el Eje Cafetero Cafetero” (2019)
This document presents a theory of the stock market andexplains its types of agents and products. Subsequently, thepaper describes the stock market transformation process inColombia and concludes with a characterization of this marketin the Colombian coffee region, highlighting the smallinvestors' role in the said market. The paper uses the results ofthe research project “Evolution of the investment alternativesin financial assets by small investors in the Coffee Regionduring the period 2002-2007,” elaborated in 2008.